Pharmacological treatment for pubertal progression in boys with delayed or slow progression of puberty: A small-scale randomized study with testosterone enanthate and testosterone undecanoate treatment - Österbrand, Martin; Fors, Hans; Norjavaara, Ensio (Frontiers in Endocrinology, 2023)
Abstract Context: The use of testosterone enanthate (TE), 50–75 mg intramuscularly (i.m.)/month, for the treatment of boys with delayed puberty or slow progression to induce puberty is standard of care in Sweden. This treatment is empirical and has not been scientifically evaluated. Replacement therapy in hypogonadal boys/young men in Sweden after induction is mainly done with testosterone undecanoate (TU), 1000 mg/3 months. TE was deregistered in Sweden 2006, therefor this study was initiated to compare the two products. Objective: To clinically evaluate pubertal progression with six injections of TE, 75 mg i.m./month (1/3-1/5 of adult dose), compared with two injections of TU, 250 mg i.m./3 months (1/4 of adult dose). Trial Design: In the Pubertal Replacement in Boys Study (PRIBS), boys aged 14–16 years in west Sweden with pubertal delay were randomized in a parallel study to TE or TU for pubertal progression. Inclusion criteria were morning testosterone levels of 0.5–3 nmol/L and testicular volume ≤6 mL. Between August 2014 and July 2019 27 boys were included. Methods: Primary outcome was testicular enlargement ≥8 mL after 12 months. TU treatment was considered clinically similar if the number of boys with testicular enlargement ≥8 mL was 80–125% of the number of boys of TE. Fisher’s exact chi-square test was used for this analysis. Results: Both treatments were well tolerated. 12/14 (86%) TU treated boys reached primary outcome and 12/12 in the TE group. Fisher’s exact chi-square testing indicated a one-sided p-value of 0.28 (the two-sided p-value was 0.483). The TU treatment was considered not clinically different from Soc. A post hoc study showed 25% power. Therefore, no evidence-based conclusion can be drawn from the results, even if the clinical data is supporting a similar effect of the treatments. Conclusion: The present small-scale study supports that both TE and TU had similar effects in terms of pubertal progression. Trial registration and founding PRIBS was a small scale academically sponsored and monitored, study. It was approved by the medical products agency in Sweden, the European Union Drug Regulating Authorities Clinical Trials Database (EudraCT) (no. 2012-002337-11) and registered in ClinicalTrials.gov NCT0541703.